Activity of Horseradish Peroxidase Adsorbed onto Titanate Nanowires - J.V. Nicolini; N.S. Resende; H.C. Ferraz (Adsorption Science & Technology, 2015)
Immobilization of horseradish peroxidase (HRP) onto titanate nanowires (TNWs) was investigated using different strategies. TNWs were synthesized by a hydrothermal method and characterized by scanning electron microscopy, X-ray diffraction, nitrogen physisorption (77K) and Fourier transform infrared spectroscopy. Free HRP was stable and active in a wide range of pH with optimal activity at 7.0. The K m of HRP with 4-aminoantipyrine and H 2 O 2 as substrate was 0.77 ± 0.25 mmol l −1 . Immobilization strategies studied were non-specific adsorption and covalent coupling through amine groups. Adsorption isotherms were well fitted by the Langmuir–Freundlich model. The coverage of TNWs containing HRP adsorbed by covalent coupling was 1.56 mg HRP m −2 and the residual enzymatic activity was approximately 40%. The enzymatic activity of free HRP and immobilized HRP was monitored as a function of storing time. The results confirm that the enzyme is firmly attached to the TNW surface through covalent binding, constituting a very promising platform for a variety of applications such as in biosensing.